2016
DOI: 10.1038/ijosup.2016.5
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin-induced satiety, a key gut servomechanism that is affected by the membrane microenvironment of this receptor

Abstract: The gastrointestinal (GI) tract has a central role in nutritional homeostasis, as location for food ingestion, digestion and absorption, with the gut endocrine system responding to and regulating these events, as well as influencing appetite. One key GI hormone with the full spectrum of these activities is cholecystokinin (CCK), a peptide released from neuroendocrine I cells scattered through the proximal intestine in response to fat and protein, with effects to stimulate gall bladder contraction and pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…HFD supplementation was also reported to secrete cholecystokinin (CCK), that responds to the intake of fat and protein. The hormone stimulates satiety after food consumption (Desai et al, 2016). The secretion CCK, which manipulates hunger, can be a tool to reduce the amount of food taken in by the body and reduce body weight, which works by preventing a positive energy balance, where the energy consumed is of greater amount compared to body metabolism and physical activity (Romieu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…HFD supplementation was also reported to secrete cholecystokinin (CCK), that responds to the intake of fat and protein. The hormone stimulates satiety after food consumption (Desai et al, 2016). The secretion CCK, which manipulates hunger, can be a tool to reduce the amount of food taken in by the body and reduce body weight, which works by preventing a positive energy balance, where the energy consumed is of greater amount compared to body metabolism and physical activity (Romieu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The allosteric modulatory effects are typically saturable, adding an additional level of safety to the effects of these agents. It has previously been suggested that pure allosteric modulators may be advantageous as CCK1R-active drugs to be used in obesity ( 34 ) - a positive allosteric modulator of CCK1R possessing no intrinsic agonist activity could enhance the satiety effect of natural CCK when it is released after a meal ( 34 ). The short half-life of circulating CCK peptides would limit the potential for side-effects relating to prolonged receptor activation, adding to the safety profile of such agents.…”
Section: Rationale For Developing Allosteric Modulators Of Cck1rmentioning
confidence: 99%
“…The peptide hormone Cholecystokinin (CCK) is well-established as being a metabolic hormone secreted from I cells of the small intestine when high levels of dietary fatty acids or proteins are detected [ 14 ]. CCK regulates digestion by stimulating the release of digestive enzymes and insulin from the pancreas and mediates satiety by binding to CCK receptors in the vagal afferent neurons of the gut–brain axis [ 15 ]. However, CCK is also a neurotransmitter, growth factor and anti-inflammatory cytokine expressed as multiple different bioactive peptides by neurons, endocrine, and epithelial cells (recently reviewed in [ 16 ]).…”
Section: Metabolic Hormones Play Roles In Modulating Macrophage Inflammatory Responsesmentioning
confidence: 99%